Part A. Taxoid synthesis: Preparation of ring A synthons and their elaboration. Part B. Synthetic studies towards the preparation of retigeranic acid A. - Tjepkema, Michael William. (University of Ottawa (Canada), 1995)
Part A. The preparation of a fully functionalized ring A of Taxol$\sp\circler$ (1), its further elaboration to the intramolecular Diels-Alder precursor 272 and the attempted cyclization of this compound are described. Allylic oxidation of the cyclohexene acetal 138 was accomplished in 65% yield using buffered selenium dioxide in toluene. Ketone 139 was converted in two steps to the vinyl ketone 197 in 33% yield. Reduction of ketone 197 occurred with excellent diastereoselectivity to furnish the allylic alcohol 198 in 96% yield. Protection and subsequent ozonolytic cleavage of 198 furnished the key intermediate aldehyde 200. Aldehyde 200 was converted through a three step sequence to the fully functionalized TMS cyanohydrin A ring compound 203. Addition of the vinyl anion derived from the bromo-diene 233 to the aldehyde 225 gave an approximately 5:1 mixture of diastereomeric alcohols 238/239 in 80% yield. Protection and separation of the major diastereomer followed by deprotection of the acetal gave the aldehyde 265 in 65% yield. Several methods were evaluated for the preparation of the dienophile component by the addition of the anions derived from dithianes 244 and 260 and (phenylselenomethyl)trimethylsilane 253. Addition of TBSCN to aldehyde 265 gave a 5:1 mixture of silyl-cyanohydrin diastereomers 268/269 with the major diastereomer 268 being isolated in 67% yield. X-ray crystallographic analysis of 268 was performed. Reduction of nitrile 268 to the aldehyde 267, addition of ethynylmagnesium chloride and Dess-Martin periodinane oxidation of the alcohols 270/271 gave the diene-dienophile ketone 272. Heating of this material in toluene in a sealed tube using "microwave assistance" failed to produce any of the desired cyclized product.* Part B. Preparation of the diene 400 and the attempted Diels-Alder cyclization of this diene to the adduct 398 is described. $\beta$-Keto-sulfone 371 was prepared in 89% yield in two steps from the vinyl-sulfide 369. Alkylation of 371 with the allylic bromide 374 followed by hydrolysis of the enol ether functionality furnished the diketone 378 in 55% yield for two steps. Intramolecular aldol-condensation and subsequent reduction gave the diol 380. Protection of the primary alcohol of 380 as a TBS ether afforded the secondary allylic alcohol 381. A variety of methods were investigated for the dehydration of alcohol 381 to the diene 383, with Grieco's procedure giving a yield of about 65%. Heating of diene 383 at $35\sp\circ$C was found to give the rearranged product 91/392. The cycloaddition of diene 383 with a number of dienophiles was investigated. Nitroethylene was found to give a mixture of unstable compounds from which no adduct could be isolated. Diene 383 underwent rearrangement to the exocyclic methylene compound 401 when Lewis acid catalysts were employed. Heating diene 400 with nitroethylene in benzene at reflux followed by treatment of the crude with potassium hydride and dimethyldioxirane gave a mixture of compounds of correct mass for structure 404 but of unproven structure.* ftn*Please refer to the dissertation for diagrams.
Keywords: Chemistry, Analytical.